2019
DOI: 10.1111/grow.12337
|View full text |Cite
|
Sign up to set email alerts
|

What drives urban population growth and shrinkage in postsocialist East Germany?

Abstract: Most cities in East Germany experienced drastic shrinkage between 1990 and 2014, but in recent years some have stabilized or even switched toward new growth paths, while others have been continuously declining. A descriptive analysis of subgroups of cities with diverging population growth trajectories reveals that this recent phase of “urban resurgence” accounts to a large share to the growth of the largest cities and some smaller cities in their hinterland and is strongly related to the residential preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 67 publications
0
17
0
1
Order By: Relevance
“…Our findings have strong implications for research on regional and urban population development (e.g., Heider, 2019b;Rees et al, 2017;Sander, 2014;Stawarz & Sander, 2020), which has in the past been strongly focused on internal migration-as primary driver of suburbanisation, counterurbanisation, and reurbanisation-as well as on the determinants of internal migration (e.g., Buch et al, 2014;Ferguson et al, 2007;Greenwood & Hunt, 1989). Concerning the latter, the question of whether economic opportunities or amenities are decisive in explaining regional disparities in migration rates has been controversially discussed in the scholarly literature.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our findings have strong implications for research on regional and urban population development (e.g., Heider, 2019b;Rees et al, 2017;Sander, 2014;Stawarz & Sander, 2020), which has in the past been strongly focused on internal migration-as primary driver of suburbanisation, counterurbanisation, and reurbanisation-as well as on the determinants of internal migration (e.g., Buch et al, 2014;Ferguson et al, 2007;Greenwood & Hunt, 1989). Concerning the latter, the question of whether economic opportunities or amenities are decisive in explaining regional disparities in migration rates has been controversially discussed in the scholarly literature.…”
Section: Discussionmentioning
confidence: 75%
“…Although the scientific debate around this question is ongoing, there exists abundant evidence that both categories are important predictors of interregional migration flows (e.g., for Germany, see Buch, Hamann, Niebuhr, & Rossen, 2014). Further, some authors have shown that the preferences for labour market and/or quality of life‐related factors vary across the different personal life cycle stages (Chen & Rosenthal, 2008; Ferguson, Ali, Olfert, & Partridge, 2007; Heider, 2019b) and socio‐economic backgrounds of migrants (Niedomysl & Hansen, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Universities and research institutes, representing the supply of jobs for researchers, are also distributed mainly in these developed cities (Franklin, 2013). The local governments should recognize that the factors shaping the distribution of researchers vary by region (Heider, 2019). For example, in the southern cities, urban consumption facilities play a more crucial role in attracting researchers, while in the northwestern cities, the number of universities and urban green land rates matters more for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…All cities of whatever size had at one time some economic role that sustained them; otherwise, they would not exist. While economic and political changes since World War II, and in Central and Eastern Europe since the end of the Communist system around 1990, have unsettled the economic functions of all cities, it is widely recognized that new economic functions, particularly those associated with the knowledge economy, have generally benefited larger cities, with smaller ones left behind (Mallach 2018;Heider 2019). In keeping with the neoliberal tendency of our times, a vocabulary of urban 'winners' and 'losers' has emerged, addressing factors such as agglomeration which favour large over small cities (Moretti 2012).…”
Section: Economic Role and Functionmentioning
confidence: 99%